The Effect of The Company's Financial Performance on Company Value With The Variable of Dividend Policy Moderation in Manufacturing Companies Listed on The Indonesia Stock Exchange - Arma Trie Nuari; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
Firm value is very important because the high value of the firm which will be followed by higher shareholder wealth. This study aims to determine the effect on the value of the company's financial performance with the dividend policy as a moderating variable. The population in this study are all manufacturing companies listed on the IDX consecutive dividend during the period 20017-2020. The results showed that: 1) Profitability significant positive effect on firm value, 2) leverage significant positive effect on firm value, 3) Liquidity not significant negative effect on firm value 4) dividend policy is not able to significantly moderate the effect of profitability on firm value 5) dividend policy is able to significantly moderate the effect of laverage on firm value, 6) Dividend policy is able to significantly moderate the effect of liquidity on firm value.